Malawi : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that Malawi's real GDP grew by an annual average of 3 percent in 2002-03. Agricultural production rebounded from the drought in 2001, but the 2004 harvest was affected by a drought. Macroeconomic imbalances, high interest rates, and infrastructure constraints have adversely affected the non-agricultural economy. Malawi's performance under the Poverty Reduction and Growth Facility (PRGF) arrangement, approved in December 2000, was disappointing. The authorities have requested IMF staff to monitor their economic program to establish a track record that could lead to a new PRGF arrangement.